Degradation study of polylactic acid, spirulina, and alginate composites in cosmetic application - Pairon, Mohammad Shahrizad; Ali, Fathilah; Anuar, Hazleen (Kulliyyah of Engineering, IIUM, 2021)
Plastic composites are suitable materials in the production of a cosmetic patch. It could be used as a matrix to hold the fiber in the composites. The fiber used in the cosmetic patch is an active ingredient that has a good reaction with the skin. However, the plastic material gives irritation and allergic when contacting the skin. Hence, the usage of biodegradable plastic such as Polylactic acid (PLA) replacing the conventional plastic in the plastic composites of the cosmetic patch. PLA has a slow degradation rate, therefore the natural fiber (spirulina and alginate) were used to increase the degradation rate of PLA. The objectives of this project were to study the degradation of the PLA composites and to characterize the surface morphology and surface properties of the degraded PLA composites. The selection of the best PLA composites is by the highest Young’s Modulus and Elongation at break value. The samples were then left for microbial degradation. The microbial degradation results showed that the spirulina enhanced PLA composite degradation. However, microbial degradation was not the best degradation method since the disturbance of alginate as a binding agent in the soil give an inconsistent result. Scanned Electron Microscopy (SEM) images showed that the fiber initiates the degradation in the PLA composites.